2023
DOI: 10.3389/fpsyg.2023.1285059
|View full text |Cite
|
Sign up to set email alerts
|

The effect of self-directed online metacognitive listening practice on Chinese EFL learners' listening ability, metacognition, and self-efficacy

Tao Pei,
Jitpanat Suwanthep,
Huashan Lu

Abstract: Research into metacognitive listening instruction under the Metacognitive Pedagogical Cycle (MPC) has been growing in recent decades, but its effects on L2 listening comprehension, metacognitive awareness, and self-efficacy remain inconclusive. In this mixed-method study, we developed a self-directed online listening practice based on the MPC and investigated its effects on 89 Chinese intermediate EFL learners over 14 weeks. Learners were assigned to either an experimental group, which used the online metacogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Despite the positive effect of self-efficacy on learners' use of self-regulate strategies (Lee et al, 2021), the impact of strategy instruction on the development of self-efficacy is inconclusive. For example, Boroumand et al (2021) found strategy-based instruction could increase learners' self-efficacy, while Fathi et al (2020), andPei et al (2023) all reported strategy training had no significant influence on learners' self-efficacy beliefs. Therefore, it is necessary to carry out further research in this regard to provide more empirical evidence on the relationship between self-efficacy and self-regulated strategy instruction.…”
Section: Theoretical Advancementmentioning
confidence: 96%
“…Despite the positive effect of self-efficacy on learners' use of self-regulate strategies (Lee et al, 2021), the impact of strategy instruction on the development of self-efficacy is inconclusive. For example, Boroumand et al (2021) found strategy-based instruction could increase learners' self-efficacy, while Fathi et al (2020), andPei et al (2023) all reported strategy training had no significant influence on learners' self-efficacy beliefs. Therefore, it is necessary to carry out further research in this regard to provide more empirical evidence on the relationship between self-efficacy and self-regulated strategy instruction.…”
Section: Theoretical Advancementmentioning
confidence: 96%